Invasive methods of hepatocellular carcinoma treatment - Gulziya Ismailova; Eugene Yenin; Shokan Kaniev; Talgat Tajibaev; Altynshash Baichalova; Almat Chormanov; Bolatbek Baimakhanov (National Scientific Medical Center, 2017)
Hepatocellular carcinoma is the fifth most common malignant neoplasm and is the third common cause of death from cancer. Despite significant advances in the development of surgical methods and new anticancer medicines, the overall survival rates HCC remain low due to high incidence of relapse or intrahepatic metastases after treatment. The mini-review is devoted to analysis of invasive treatment methods hepatocellular carcinoma for determining the tactics of surgical treatment.